2018
DOI: 10.1037/fam0000426
|View full text |Cite
|
Sign up to set email alerts
|

The trajectory of coparenting relationship quality across early adolescence: Family, community, and parent gender influences.

Abstract: This study examined longitudinal change in coparenting support and conflict for married parents during their child's adolescence, and the links between financial, work, and community factors and coparenting support and conflict. We utilized an ecological perspective, drawing on five waves of data from 635 dual-earner families with adolescents (M = 11.29, SD = .48 years old at Time 1). Applying a multilevel modeling approach and using reports from mothers and fathers we examined: (a) change in coparenting suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 55 publications
3
19
2
2
Order By: Relevance
“…One of the longstanding questions in adoption research is whether, and the extent to which, adopted children are able to adjust to the new family and to define a sense of belonging. Specifically, a significant portion of adoption research revealed that adoptees are at higher risk for difficulties than is the general population (e.g., Askeland et al, 2018; Barroso et al, 2017; Juffer & Van IJzendoorn, 2005; Riina & Feinberg, 2018). It is worth noting, however, that, when compared with peers who have remained in residential care, adoptees appear to be better adjusted and to show a cognitive advantage (Sánchez‐Sandoval, 2015; van IJzendoorn et al, 2005), thus supporting the claim that adoption is a crucial source of resilience and represents an opportunity for children out‐of‐home care to recover their physical, cognitive, and socio‐emotional development (Barroso et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…One of the longstanding questions in adoption research is whether, and the extent to which, adopted children are able to adjust to the new family and to define a sense of belonging. Specifically, a significant portion of adoption research revealed that adoptees are at higher risk for difficulties than is the general population (e.g., Askeland et al, 2018; Barroso et al, 2017; Juffer & Van IJzendoorn, 2005; Riina & Feinberg, 2018). It is worth noting, however, that, when compared with peers who have remained in residential care, adoptees appear to be better adjusted and to show a cognitive advantage (Sánchez‐Sandoval, 2015; van IJzendoorn et al, 2005), thus supporting the claim that adoption is a crucial source of resilience and represents an opportunity for children out‐of‐home care to recover their physical, cognitive, and socio‐emotional development (Barroso et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Studies about coparenting among heterosexual couples across childhood and adolescence have uncovered different trajectories related to parental gender (Cowan, Cowan, & Kerig, 1993; Riina & Feinberg, 2018). Thus, research investigating coparenting and children’s development in families diverse in parental gender and sexual orientation (i.e., those with same- and different-sex parents) could broaden understanding regarding effects of coparenting on children, yet no such studies are available in families diverse in parental sexual orientation beyond the preschool years (Farr & Patterson, 2013).…”
mentioning
confidence: 99%
“…Among heterosexual couples, it has long been asserted that men have greater relationship satisfaction than women (Greil et al, 2018;Jackson, Miller, Oka, & Henry, 2014). A recent study found that women experienced higher levels of stress and lower levels of relationship satisfaction than men (Riina & Feinberg, 2018). Compared to different-sex couples, same-sex couples are supposed to be more fluid with respect to gender dynamics and scripts.…”
Section: Sex As a Moderatormentioning
confidence: 99%